CLINICAL DETERIORATION OF THE ONCOLOGY CHILD: RELIABILITY OF A NEW TOOL ADAPTED FROM THE BRIGHTON PEDIATRIC EARLY WARNING SCORE - Soares, Nataly Tsumura Inocêncio; Soares, Marcos Hirata; Pimenta, Rosângela Aparecida (Cogitare Enfermagem, 2024)
Objective: To measure the degree of reliability of the construction of new items and the adaptation of the Brighton Pediatric Early Warning Score for children with cancer. Method: Methodological study to analyze the equivalence of inter-judge content regarding the inclusion of items in the scale to detect early clinical deterioration in children with cancer: signs of bleeding, changes in temperature, and presence of grade III/IV mucositis. The Intraclass Correlation Coefficient and Cronbach’s Alpha were used for analysis, considering a value ≥0.750. Results: Based on the judges’ feedback, the items proposed for inclusion were retained, with minor adjustments to the scores. Thirty nurses (86.1%) and six doctors (13.9%) from Brazil evaluated the scale, resulting in an intraclass correlation coefficient of 0.823. Conclusion: The instrument proved suitable, with theoretical relevance and practical application, for early detection of clinical deterioration in children with cancer. To this end, it contributes to timely identification by the team, minimizing unfavorable outcomes.